Medical imaging signals and systems - Prince, Jerry L.; Links, Jonathan M. (Pearson, 2015)
This text is designed for courses in medical imaging systems. It is also suitable for professionals seeking an overview of medical imaging systems. With signal processing as its foundation, Medical Imaging Signals and Systems, Second Edition covers the most important imaging modalities in radiology: projection radiography, x-ray computed tomography, nuclear medicine, ultrasound imaging, and magnetic resonance imaging. Organized into parts to emphasize key overall conceptual divisions, Medical Imaging is most appropriate for engineering students who have taken the prerequisite signals and systems courses as well as elementary probability.